Analysis of the Business Assistance Program on the Development of MSME Customers of Bank X in Pamotan Branch - Cahyanti, Pidie Tri; Ismayantika Dyah Puspasari (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: The purpose of this study is to analyze the Business Assistance Program on the development of micro, small, and medium enterprises (MSMEs) of bank X customers in Pamotan branch. Design/Method/Approach: This research uses a qualitative approach, where I obtained information through observation at the business place and conducted interviews as well as direct documentation to 4 informants, namely business owners as well as bank X customers at the Pamotan branch who are participating in the business assistance program. Research Finding: The results of this study are that MSME players as well as customers of Bank X have participated in a business mentoring program, where this program is considered quite helpful for the development of their MSMEs. This is because with this business mentoring program, they get new knowledge to advance the MSMEs that they have been running for years. If seen from one side, customers initially thought that this business mentoring program would be boring and a waste of time. However, after they went through it to the end, the customers felt satisfied and happy because the material taught during this mentoring program could help the progress of their MSMEs. Not only do they get learning material, they also practice the results of learning material from the business mentoring program that they have undergone. When viewed from the other side, this program has a weakness where the mentoring program time is limited and is felt to be lacking for customers so that it may be a little less than optimal. In addition, there is limited customer business capital and several other factors that make customers only able to practice mentoring program material that does not require large costs. Theoretical contribution/Originality: This research is expected to be able to add information about business assistance programs on the development of micro, small and medium enterprises (MSMEs) of X bank customers. Practitionel/Policy implication: For MSME owners as well as Bank X customers, it is hoped that this research can provide input in the form of advice and information to business owners regarding the importance of business assistance programs held by Bank X to its customers for the development of their MSMEs. For readers, this research is expected to be a reference for those who are interested in conducting research related to the analysis of business assistance programs on the development of MSMEs of Bank X customers. And for Bank X, this research is expected to be an input or solution for the development of business assistance programs for customers so that they can be more developed and Bank X always supports the sustainability of MSMEs, especially the businesses of Bank X customers. Research limitation: The limitation in this study is the limited practice carried out by customers after learning the material due to limited business capital so that customers only carry out practices that do not require a lot of capital so that the research results from the analysis of the business assistance program on the development of MSMEs of Bank X customers are less than optimal.